Kultúrne dedičstvo v kontexte zaniknutého baníctva v meste Banská Štiavnica - Darulová, Jolana (Studia Etnologiczne i Antropologiczne, 2014)
The city of Banska Stiavnica and technical monuments in its vicinity were in year 1993 registered in the List of the World Cultural Heritage UNESCO (the mining region). The Salamander Parade in Banska Stiavnica as part of intangible cultural heritage of Slovakia represents specific and unique cultural traditions of miners that had formed during 150 years of existence of the Academy of Mining in Banská Stiavnica, during the following 80 years of active mining, and moreover, during 20 years following its finishing in 1993. The “Ausus” tradition nominated by the mining association Herrengrund is located in the mining settlement of Spania Dolina.